2010
DOI: 10.1021/jf903898t
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Pyrazines in Maillard Model Systems of Lysine-Containing Dipeptides

Abstract: Whereas most studies concerning the Maillard reaction have focused on free amino acids, little information is available on the impact of peptides and proteins on this important reaction in food chemistry. Therefore, the formation of flavor compounds from the model reactions of glucose, methylglyoxal, or glyoxal with eight dipeptides with lysine at the N-terminus was studied in comparison with the corresponding free amino acids by means of stir bar sorptive extraction (SBSE) followed by GC-MS analysis. The reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 37 publications
1
81
0
4
Order By: Relevance
“…Reaction products of the methylglyoxal/AS system listed in Table 2 are very typical Maillard reaction products, observed in both cloud water simulations Lin et al, 2015;Sareen et al, 2010;Hawkins et al, 2016) and the chemical characterization of baked bread, cooked meat, aged cheese and other reactions between carbonyl containing compounds and 30 amines or amino acids (Koehler and Odell, 1970;Adams et al, 2008;Van Lancker et al, 2010;Divine et al, 2012). It is therefore surprising that pyrazine-based products, which are also well-known to form in Maillard reactions in food, have not been identified in the context of atmospheric reactions.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Reaction products of the methylglyoxal/AS system listed in Table 2 are very typical Maillard reaction products, observed in both cloud water simulations Lin et al, 2015;Sareen et al, 2010;Hawkins et al, 2016) and the chemical characterization of baked bread, cooked meat, aged cheese and other reactions between carbonyl containing compounds and 30 amines or amino acids (Koehler and Odell, 1970;Adams et al, 2008;Van Lancker et al, 2010;Divine et al, 2012). It is therefore surprising that pyrazine-based products, which are also well-known to form in Maillard reactions in food, have not been identified in the context of atmospheric reactions.…”
mentioning
confidence: 79%
“…This mechanism is described as "the most accepted formation mechanism for pyrazine" in Maillard reactions in food (Adams et al, 2008;Van Lancker et al, 2010) Divine et al (2012) showed that among the four possible mechanisms of alkylpyrazine formation in aged Parmesan cheese, only the methylglyoxal-based mechanism correctly explains the observed products. Third, 2,5-DMP in particular has been shown to form in focused studies of Maillard reactions in food, specifically in cases where methylglyoxal was exposed to amine-containing compounds (Adams et al, 2008;Van Lancker et al, 2010;Divine et al, 2012;Yu et al, 2017). In Van Lancker et al (2010), the reaction of methylglyoxal with heated free amino acids and lysine containing dipeptides 25 produced 2,5(6)-DMP and trimethylpyrazine at 10-100 fold times the signal of other pyrazines.…”
Section: Pyrazine-based Chromophoresmentioning
confidence: 98%
See 2 more Smart Citations
“…[20,21] Pyrazines commonly provide a roasted flavor and a nutty and toasted odor. [22,23] Some studies have reported that pyrazines smell like roasted potato, [23] and have been studied principally in virtue of their characteristic flavor notes in various foods. [19] Esters such as hexyl acetate, present in seafood products, are associated with fruity sensory notes.…”
Section: Volatile Compounds In Antarctic Krill As Analyzed By Hs-spmementioning
confidence: 99%